RECENT AND FUTURE DEVELOPMENT OF PLC IN INDUSTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
From 1983 the industry started using PLC on small scale but after development in industry. the plc became the most important part of industry .for achieving industry 4.0 opportunities PLC played important role in automation and controlling different process as the necessities of automation increase day by day the control system need easily ,reliable, cheap programmable device and these done by using programmable logic controller. The now in different industry the PLC easily communicate with HMI and performed the various process of with less time without operator for e.g. Counting of engine in mechanical company. Sun tracking, motor control etc. in electrical company done by the PLC. In this paper authors studied the overview of the necessities and application of PLC in industry .The purpose of this study is to knowing about recent and future trends in PLC. With these information how authors can improve the recent trends with help our fresh knowledge.